Identification and comparison of allergenicity of native and recombinant fish major allergen parvalbumins from Japanese flounder (Paralichthys olivaceus). Issue 10 (25th September 2019) - Sun, Lirui; Xu, Lili; Huang, Yuhao; Lin, Hong; Ahmed, Ishfaq; Li, Zhenxing
Abstract : Compared with native parvalbumin, recombinant β-parvalbumin based on the optimized DNA sequence can be used in fish allergen confirmation. Abstract : Parvalbumin is the major fish allergen that can trigger anaphylactic reactions in predisposed individuals. We extracted and purified native parvalbumins from Japanese flounder ( Paralichthys olivaceus ) with gradient ammonium sulfate fractionation, and cloned DNAs into the expression vector pET-28a (+) to produce highly purified recombinant parvalbumin in Escherichia coli. The identification of native and recombinant parvalbumins was performed by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), immunoblotting, and mass spectrometry. The IgG-binding capacity was examined by indirect and inhibition ELISA. The immuno-reactivity was further evaluated by the release assay of β-hexosaminidase in an RBL-2H3 cell model. Three parvalbumin isoforms were purified, namely PVI, PVII and PVIII with a purity of over 90%. Mass data showed that PVII and PVIII matched with XP_019958408.1 and XP_019938975.1 in the NCBI database, respectively. The recombinant parvalbumin was successfully expressed with high purity and matched with PVIII, which has been proved as the major parvalbumin isoform. Data from an ELISA assay revealed that the recombinant PVIII contains most of the IG-binding epitopes of the native PVIII. Meanwhile, the recombinant PVIII showed a lower immuno-reactivity in the RBL-2H3 cell model. The results suggest that recombinant PVIII could be a useful tool for the confirmation of fish allergens and diagnosis of fish allergies.